PENGEMBANGAN SUATU MODEL SIMETRI KIRI-KANAN DAN IMPLIKASINYA - , Qidir Maulana Binu Soesanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
We have perfecting model that develop by Ferdiyan which is base on SU(2)L âSU(2)Râ U(1)I gauge, that previosly contains anomalies. For perfecting this model we add new particles with very heavy masses on the quark sector. It can be shown that those particles will decay and interact to become particles of the standard model which have small masses. So this model in the low energy scale will reduce to the standard model.